Auction Of The Executed Collateral Object Under Fiduciary Guarantee - Kurniawati, Dewi; Saleh, Moh (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research endeavors to analyze two crucial aspects within the legal framework of Indonesia, primarily in response to Constitutional Court Decision Number 18/PUU-XVII/2019. First, it delves into the coercive power of debtors regarding the surrender of fiduciary guarantee objects and examines the implications of the Constitutional Court's ruling, which allows debtors the choice not to voluntarily relinquish collateral objects, thus introducing ambiguity regarding the obligations outlined in Article 30 of the Fiduciary Guarantee Law. Consequently, this decision extends the execution process, increases costs, dampens the business climate, and diminishes potential Non-Tax State Revenue. Furthermore, creditors are challenged in executing defaults, now necessitating court orders and rendering the once-efficient process laborious. Second, the research navigates the intricacies of conducting auctions for executed fiduciary guarantee objects, elucidating the legal framework governing auctions in Indonesia, where transparency, competition, certainty, accountability, and efficiency are paramount. The study unveils the procedure for initiating auctions, the criteria for prospective participants, and the guiding principles of these auctions. In conclusion, this research calls for comprehensive studies by policymakers prior to any revisions in the Fiduciary Security Law, given the growing diversity of collateral objects and the complexities stemming from Constitutional Court Decision Number 18/PUU-XVII/2019. It underscores the need to modernize movable property security laws to adapt to evolving societal dynamics, consolidate fiduciary security regulations, and streamline the procedures for auctioning executed fiduciary collateral objects